Finger Puppet Media Boosts Preschool Speaking Skills: Research Findings: Meningkatkan Kemampuan Berbicara Anak Prasekolah dengan Media Boneka Jari: Penelitian Tindakan Kelas - Jannah, Alfun Nisa’ Ahlul; Aulina, Choirun Nisak (Indonesian Journal of Education Methods Development, 2023)
This study aimed to investigate the efficacy of finger puppet media in improving the speaking abilities of children aged 3-4 years in a playgroup setting at KB 'Aisyiyah 02 Maduran, Lamongan Regency. Employing the Classroom Action Research approach over two cycles, the research involved three stages: pre-cycle, cycle I, and cycle II. Through the use of finger puppets, teachers encouraged children to engage in verbal expression, question-asking, and storytelling, making the learning experience enjoyable and captivating. The results demonstrated significant progress, with the overall speaking skill value increasing from 35.54% in the pre-cycle to 80.56% in cycle II. This study highlights the potential of finger puppet media in promoting effective communication skills among young children, providing valuable implications for early childhood education and language development.